Serological, Molecular and Culture-Based Diagnosis of Lentiviral Infections in Small Ruminants - Aphrodite I. Kalogianni; Ioannis Stavropoulos; Serafeim C. Chaintoutis; Ioannis Bossis; Athanasios I. Gelasakis (Viruses, 2021)
Small ruminant lentiviruses (SRLVs) infections lead to chronic diseases and remarkable economic losses undermining health and welfare of animals and the sustainability of farms. Early and definite diagnosis of SRLVs infections is the cornerstone for any control and eradication efforts; however, a “gold standard” test and/or diagnostic protocols with extensive applicability have yet to be developed. The main challenges preventing the development of a universally accepted diagnostic tool with sufficient sensitivity, specificity, and accuracy to be integrated in SRLVs control programs are the genetic variability of SRLVs associated with mutations, recombination, and cross-species transmission and the peculiarities of small ruminants’ humoral immune response regarding late seroconversion, as well as intermittent and epitope-specific antibody production. The objectives of this review paper were to summarize the available serological and molecular assays for the diagnosis of SRLVs, to highlight their diagnostic performance emphasizing on advantages and drawbacks of their application, and to discuss current and future perspectives, challenges, limitations and impacts regarding the development of reliable and efficient tools for the diagnosis of SRLVs infections.